Hyperbaric oxygen therapy as an adjunct to corticosteroid treatment in sudden sensorineural hearing loss: a retrospective study - Skarzynski, Piotr H.; Kolodziejak, Aleksandra; Gos, Elżbieta; Skarzynska, Magdalena B.; Czajka, Natalia; Skarzynski, Henryk (Frontiers in Neurology, 2023)
Background: A retrospective clinical study was conducted to test the impact of including oxygen hyperbaric oxygen treatment (HBOT) for treating patients with sudden sensorineural hearing loss (SSNHL). Materials and Methods: 63 adult patients with SSNHL diagnosed between 2015 and 2023 were divided into two groups: 36 patients treated with intratympanically and orally administered glucocorticoid together with hyperbaric oxygen therapy (HBOT); and 27 patients treated with intratympanically and orally administered glucocorticoid (without HBOT). Audiological evaluation was performed using pure-tone audiometry. Results: Average hearing gain as measured by pure tone average was 12.5 dB HL (± X dB) in the patients treated with steroids combined with HBOT, oxygen and 14.1 dB HL (±Y dB) in the patients treated with steroids alone. Successful treatment (complete recovery or marked improvement) was observed in 27.8% of the patients in the first group and 25.9% in the second group. There was no statistically significant difference between the groups. Conclusion: Both groups of patients – those treated with glucocorticoids and those treated with glucocorticoids and HBOT – had similar hearing outcomes. A prospective, controlled, and randomized study would provide more reliable knowledge about HBOT in SSNHL. .